Competency‐based assessment in nutrition education: A systematic literature review. Issue 1 (19th September 2021) - O'Donovan, Sarah; Palermo, Claire; Ryan, Lisa
Abstract: Background: A suitably prepared and qualified nutrition and dietetics workforce is part of the solution to combating the burden of disease. Competency‐based assessment is a key part of the education of future workforces. Although there has been recent attention on competency‐based assessment in dietetics, there is little exploration of competency‐based education for the preparation of nutritionists. The present study aimed to understand how competency‐based assessment is implemented and evaluated in nutrition education. Methods: A systematic literature review was carried out according to PRISMA guidelines. Four databases were initially searched in February 2020 using key words related to competenc* in combination with nutrition or dietetic and their synonyms. An updated search was completed again in March 2021. Studies that met eligibility criteria where the focus was on nutrition and involved a method of competency‐based assessment were synthesised narratively. Results: From a total of 6262 titles and abstracts, six studies on competency assessment in nutrition education were identified. The assessments focused on the development of key skills, including motivational interviewing and nutrition assessment, changes to knowledge and attitudes on food and culture, and self‐perceived development of communication, collaboration, management, advocacy, scholarship and professional capabilities. No studies were found that assessed promotion of health and wellbeing or the food chain competencies. Conclusions: The lack of research in competency‐based assessment must be addressed to ensure we are effectively preparing future nutritionists for work such that they can impact health outcomes. Abstract : Competency‐based assessment in nutrition.